GUGATAN PEMBATALAN IZIN MENDIRIKAN BANGUNAN HOTEL SALAK TOWER - Geraldy Mista Putera; Yuwono Prianto (Fakultas Hukum Universitas Tarumanagara, 2019)
Development is mostly carried out in aspects of human life to develop the economy and improve people's welfare. This construction is build upon permit in the form of a building permit issued by the government. The permit can also be canceled if it is deemed not in accordance with the applicable requirements. The goal of this investigation is to determine the resolution of the case and to find out whether the legal considerations given by the judge are correct or not. This investigation utilize normative legal research methods. The origin of legal material used in the research are primary legal library materials, secondary legal library materials, and tertiary legal library materials. This investigation used qualitative analysis. Based on an analysis of the sources of legal material that has been carried out, the authors conclude that the lawsuit against the cancellation of the building permit was registered past the deadline for the issuance date of the permit or has passed since the permit was announced at the time of the first construction, then the perceived loss the plaintiff is considered not a material loss and only concerned with the interests of one of the plaintiffs. As well as the legal considerations that have been conveyed, it is considered appropriate and when looking at the spatial plan of the Bogor Regency area, the location where the hotel is built is included in the area that allows for hotel buildings.